2022
DOI: 10.1021/acssuschemeng.2c00061
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals from Sugar Cane Bagasse Using Organic and/or Inorganic Acids: Techno-Economic Analysis and Life Cycle Assessment

Abstract: The isolation of cellulose nanocrystals (CNCs) by organic acid hydrolysis can contribute to reducing the extensive use of mineral acids, but aspects related to performance, cost effectiveness, and sustainability still need to be addressed. Here, techno-economic analysis (TEA) and life cycle assessment (LCA) were performed to evaluate the production of CNCs using organic and/or inorganic acid hydrolysis, in the context of a sugar cane biorefinery. CNCs were extracted from sugar cane bagasse using sulfuric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…Concerning CitCNC extraction (S3), the hydrolysis step was the most dominant contributor (Figure 7b) due to the usage of citric acid, whose production contributes to all 16 impact categories. A similar finding is reported by Bondancia et al 29 . A contribution analysis of S1 and S2 can be found in SI (Figure S7-S8).…”
Section: Guiding Process Development By Life Cycle Assessmentsupporting
confidence: 92%
See 2 more Smart Citations
“…Concerning CitCNC extraction (S3), the hydrolysis step was the most dominant contributor (Figure 7b) due to the usage of citric acid, whose production contributes to all 16 impact categories. A similar finding is reported by Bondancia et al 29 . A contribution analysis of S1 and S2 can be found in SI (Figure S7-S8).…”
Section: Guiding Process Development By Life Cycle Assessmentsupporting
confidence: 92%
“…7b) due to the usage of citric acid, whose production contributes to all 16 impact categories. A similar nding is reported by Bondancia et al 29 A contribution analysis of S1 and S2 can be found in ESI (Fig. S7 and S8 †).…”
Section: Colloidal Stabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…Research studies have looked into the idea of employing different mineral or organic acids as an alternative to the conventional sulfuric acid approach to producing CNC. Techno-economic analysis (TEA) by Bondancia et al [277] revealed that the cost of the citric acid applied in the hydrolysis had a significant effect on the minimum selling price (MSP) of CNC, which was relatively higher at USD 16,460 per dry ton. The capital cost of CNC production via citric acid hydrolysis was USD 7,000,000, which was comparatively lower.…”
Section: Economic Assessment Of the Nanocellulose Extraction Processmentioning
confidence: 99%
“…Despite the fact that ion-exchange resin adsorption yields high selectivity and efficiency, the resins need to be continually replaced and regenerated, which results in the generation of a substantial volume of solid and liquid waste . Furthermore, membrane separation techniques such as ultrafiltration, electrodialysis, electrodeionization, and perstraction are considered as potential ways for recovering CA from fermentation broth. In their works, CA recovery has been dominated by the electrodialysis method using bipolar membranes, which relies on the electromigration of ions across ion exchange membranes for the separation of impurities and organic acid concentration from an aqueous solution. However, these techniques still have limitations that restrict them from being used in large-scale production, including the stability and cost of the membranes, use of harmful chemicals, and high-power consumption.…”
Section: Introductionmentioning
confidence: 99%